Using blogs to support practical teaching of educational technology. (1st January 2013) - Han, Xiaoling
Practical teaching plays an important role in cultivating inter-disciplinary and application-oriented talents in the domain of educational technology. The purposes of this study are to explore the use of blogs in helping practical teaching of educational technology, and to investigate how to promote students-teacher interaction by using the blogs and the roles of the teacher. 89 students in 30 groups from two classes participated in this study. Two class blogs were used as a communication tool for sharing resources. A questionnaire and the posts on the blogs were used for data collection. The result showed that the use of the blogs was helpful for supporting practical teaching and it was easier for the teacher to track and monitor students' learning processes by using the blogs. Also, the blogs played an important role especially in communicating, recording, sharing, and reflecting. Issues involved in roles of teacher are discussed.